How Is the Norepinephrine System Involved in the Antiepileptic Effects of Vagus Nerve Stimulation? - Berger, Alexandre; Vespa, Simone; Dricot, Laurence; Dumoulin, Manon; Iachim, Evelina; Doguet, Pascal; Vandewalle, Gilles; El Tahry, Riëm (Frontiers in Neuroscience, 2021)
Vagus Nerve Stimulation (VNS) is an adjunctive treatment for patients suffering from inoperable drug-resistant epilepsy. Although a complete understanding of the mediators involved in the antiepileptic effects of VNS and their complex interactions is lacking, VNS is known to trigger the release of neurotransmitters that have seizure-suppressing effects. In particular, norepinephrine (NE) is a neurotransmitter that has been associated with the clinical effects of VNS by preventing seizure development and by inducing long-term plastic changes that could restore a normal function of the brain circuitry. However, the biological requisites to become responder to VNS are still unknown. In this review, we report evidence of the critical involvement of NE in the antiepileptic effects of VNS in rodents and humans. Moreover, we emphasize the hypothesis that the functional integrity of the noradrenergic system could be a determining factor to obtain clinical benefits from the therapy. Finally, encouraging avenues of research involving NE in VNS treatment are discussed. These could lead to the personalization of the stimulation parameters to maximize the antiepileptic effects and potentially improve the response rate to the therapy.